How Regulatory Capture Which Prioritizing Private Sector Interests Exists in Indonesian Democracy - Ekawestri Prajwalita Widiati (Business and Human Rights Law & Policy, 2025)
Indonesia takes pride in its status as a democratic state. Democracy is a fundamental principle reflected in the nation’s philosophical theory, deemed as Pancasila and embedded in its fourth principle, enunciating “democracy guided by the inner wisdom in the unanimity arising out of deliberations among representatives”. Significant changes made to the legislation-making process have led to the expectation that this increased democratic framework will concurrently enhance public participation. However, its status quo begs to differ as Indonesia may be witnessing a parliament that is gradually transitioning back to the New Order regime. Although its legislative process has ostensibly become democratic, the parliament has seemingly functioned as a forum that represents interests that are increasingly business- and profit-oriented. Data collected by Yayasan Auriga Nusantara and Tempo further show that the names of Parliament members are recorded in 1.106 companies in several sectors. The composition of the current parliament, with some having close connections with businesses, entailing prioritization of private over public interests, illustrates the regulatory capture phenomena. Signs of regulatory capture, substantiated by the lack of public participation in Indonesia’s legislative process, are paradoxical to its supposedly ‘democratic’ system. This paper, therefore, aims to demonstrate that Indonesia’s current legislation-making process does not enhance public participation, despite it having been engineered into a democratic procedure through the amendments to the 1945 Constitution and relevant statutory laws. It is found that democracy does not guarantee increased participation but may be used to obscure oligarchy and private interests. This entails a legislation-making process that is inherently captured by business interests. A lack of public participation does not always indicate the absence of a particular group’s involvement but can also denote that no genuine consideration is made towards its interests.